Ontogenetic Expression of Sonic Hedgehog in the Chicken Subpallium - Bardet, Sylvia M.; Ferran, José L.; Sanchez-Arrones, Luisa; Puelles, Luis (Frontiers in Neuroanatomy, 2010)
Sonic hedgehog (SHH) is a secreted signaling factor that is implicated in the molecular patterning of the central nervous system (CNS), somites and limbs in vertebrates. SHH has a crucial role in the generation of ventral cell types along the entire rostrocaudal axis of the neural tube. It is secreted early in development by the axial mesoderm (prechordal plate and notochord) and the overlying ventral neural tube. Recent studies clarified the impact of SHH signaling mechanisms on dorsoventral patterning of the spinal cord, but the corresponding phenomena in the rostral forebrain are slightly different and more complex. This notably involves separate Shh expression in the preoptic part of the forebrain alar plate, as well as in the hypothalamic floor and basal plates. The present work includes a detailed spatio-temporal description of the singular alar Shh expression pattern in the rostral preoptic forebrain of chick embryos, comparing it with FoxG1, Dlx5, Nkx2.1 and Nkx2.2 mRNA expression at diverse stages of development. As a result of this mapping, we report a subdivision of the preoptic region in dorsal and ventral zones; only the dorsal part shows Shh expression. The positive area impinges as well upon a median septocommissural preoptic domain. Our study strongly suggests tangential migration of Shh positive cells from the preoptic region into other subpallial domains, particularly into the pallidal mantle and the intermediate septum.